2018
DOI: 10.3389/fmicb.2018.01400
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Fungal Communities in Heshang Cave of Central China Revealed by Mycobiome-Sequencing

Abstract: Deciphering of the mycobiome in pristine karst caves has been impeded by constraints of remote locations, inaccessibility to specimens and technical limitations, which greatly restricted in-depth understanding of mycobiomes in subterranean ecosystem. Here, mycobiomes of Heshang Cave in south-western karst region of China were investigated by Illumina HiSeq sequencing of fungal rRNA-ITS1 gene across different habitats. In total 793,502 ITS1 reads and 2,179 OTUs from 778 Mb reads after stringent quality control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 66 publications
5
27
1
Order By: Relevance
“…DNA was extracted from 0.5 g of rumen contents per sample after thawing and mixing well, with the E.Z.N.A DNA kits for soil, following the manufac turer's introduction. PCR was conducted using universal fungal primers for ITS1, which are as follows: forward primer ITS1 5'-GGAAGTAAAAGTCGTAACAAGG-3' and reverse primer ITS2 5'-GCTGCGTTCTTCATC-GATGC-3' (Man et al 2018). Each tube for amplification contained 4 µl 5 × FastPfu Buffer, 2 µl dNTPs at a concentration of 2.5 mM, 0.8 µl each primer at a concentration of 5 uM, 0.4 µl FastPu polymerase, and 10 ng DNA template with double-distilled H 2 O (ddH 2 O) added to 20 µl.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA was extracted from 0.5 g of rumen contents per sample after thawing and mixing well, with the E.Z.N.A DNA kits for soil, following the manufac turer's introduction. PCR was conducted using universal fungal primers for ITS1, which are as follows: forward primer ITS1 5'-GGAAGTAAAAGTCGTAACAAGG-3' and reverse primer ITS2 5'-GCTGCGTTCTTCATC-GATGC-3' (Man et al 2018). Each tube for amplification contained 4 µl 5 × FastPfu Buffer, 2 µl dNTPs at a concentration of 2.5 mM, 0.8 µl each primer at a concentration of 5 uM, 0.4 µl FastPu polymerase, and 10 ng DNA template with double-distilled H 2 O (ddH 2 O) added to 20 µl.…”
Section: Methodsmentioning
confidence: 99%
“…Han and coworkers research has shown that the concentrated feed has an important impact on the anaerobic fungal population of cashmere goats AF (Han et al 2019). AF secrete a range of cell wall degrading enzymes such as free enzymes and cellulase multienzyme complexes (Cheng et al 2018), which are effective degradation products of plant biomass (Haitjema et al 2014). Screening of all rumen microbial CAZyme transcripts indicated that the AF of Neocallimastigaceae produced the largest share of cellulase transcripts (Söllinger et al 2018).…”
mentioning
confidence: 99%
“…Cave walls had the highest fungal diversity while overall bats had the lowest. Fungal diversity on cave walls in China was also higher compared to other cave substrates, such as sediments and air [6]. However, while [37] found that bacterial diversity was higher on cave walls compared to bats, fungal diversity was similar.…”
Section: Discussionmentioning
confidence: 90%
“…Despite the apparent lack of organic material, a diverse fungal assemblage has previously been documented on cave walls [3][4][5][6]. In [7], it was found that fungal diversity on cave walls differed from that on the floor of caves.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important topics in the conservation of caves with Paleolithic paintings is the assessment of the microbial communities inhabiting speleothems, rocks, water pools and air. A wide diversity of approaches on cave fungi can be found in the literature [1][2][3][4][5][6] and aerobiological studies were introduced as a management tool to control airborne fungi in caves with paintings [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%